IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN ADMINISTRASI SISTEM JARINGAN DI SMK NEGERI 1 PAPALANG - Siti Rahmawati; Abdul Muis Mapalotteng; Siti Aisyah Hading (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
The research objectives are (1) to determine the level and (2) differences in average activities and student learning outcomes in classes that apply the project-based learning model and classes that do not apply project-based learning. This type of research is experimental. Using a quantitative approach. The research objects are students and class teachers. The research methodology is observation tests and interviews, where the frequency of students in the experimental class is more dominant in getting category C pretest scores, namely 22 people out of a total of 29 people in the entire experimental class. Then the frequency of students in the control class also dominantly got grades in category C, namely 18 people out of a total of 29 students. The results of the research are (1) There is a difference in the average value of student learning outcomes between classes that apply project-based learning methods (experiment) and classes that do not receive treatment (control). This is reinforced by the description of the average score of experimental class students as 86.89, higher than the control class, namely 68.67. (2) There is a difference in the average student learning activity between classes that apply project-based learning methods (experiment) and classes that do not receive treatment (control). This is reinforced by the description of the average activity of experimental class students as 76.83, higher than the control class, namely 65.52. The research results indicate that implementing a project-based learning model can help increase student activities and grades in the network system administration subject at SMK N 1 Papalang. Suggestions are (1) Teachers can maximize the quality of learning through implementing the project-based learning model, (2) Through the project-based learning model, they can improve students' critical attitudes and learning activities, (3) Teachers should study the project-based learning model more deeply to broaden their knowledge. teachers regarding project based learning models